Caracterização das potencialidades e fragilidades ambientais do meio físico de parte do município de Santa Rita do Passa Quatro (SP) - Lossardo, Luiz Fernando (2010)
The climatic resort of Santa Rita do Passa Quatro-SP, located in the north-east region of the state of Sao Paulo, has about 27,500 inhabitants, as well as other cities of the country, reserved its right proportions, currently suffers from several problems of urban and environmental degradations, which are often caused by human action, mainly by the indiscriminate appropriation of their territories. It is known that in the face of intense population growth in the period of industrialization, coupled with a lack of commitment of some municipal administrations with the urbanenvironmental zoning, the territorial planning, the production of space in cities, etc., many cities live great mistake processes of occupation and without any concern for sustainable development. Thus, in order to recover the vitality of the degraded environment and the quality of life of its inhabitants, some brazilian cities are already taking very important decisions to realize their strategic planing, master plans, etc. Therefore, the characterization of the potentiality and environmental fragility of the physical environment of the cities are key to subsidize their urbanenvironmental planning, is also an important tool to aid in monitoring the land occupation in its urban and suburban regions in a technically adequate. Thus, this study aims to characterize the potentiality and environmental fragility of the part physical environment of the city of Santa Rita do Passa Quatro, in order to provide information that can subsidize studies of urban planning, territorial planning and also other related studies the identification, mitigation of environmental problems and guidelines for the prevention of future problems in the physical occupation of the region studied.